Metabolomics-Based Investigation on the Metabolic Changes in Crassostrea gigas Experimentally Exposed to Galvanic Anodes - Nathalie Imbert-Auvray; Denis Fichet; Pierre-Edouard Bodet; Pascaline Ory; René Sabot; Philippe Refait; Marianne Graber (Metabolites, 2023)
Cathodic protection is widely used to protect metal structures from corrosion in marine environments using sacrificial galvanic anodes. These anodes, either in Zinc, or preferentially nowadays in Al-Zn-In alloys, are expected to corrode instead of the metal structures. This leads to the release of dissolved species, Zn2+, Al3+, and In3+, and solid phases such as Al(OH)3. Few studies have been conducted on their effects on marine organisms, and they concluded that further investigations are needed. We therefore evaluated the effects of Zn and Al-Zn-In anodes on oysters stabulated in tanks, under controlled conditions defined through a comparison with those prevailing in a given commercial seaport used as reference. We analyzed the entire metabolome of gills with a non-targeted metabolomic approach HRMS. A modelling study of the chemical species, corresponding to the degradation products of the anodes, likely to be present near the exposed oysters, was also included. We identified 16 and two metabolites modulated by Zn- and Al-Zn-In-anodes, respectively, that were involved in energy metabolism, osmoregulation, oxidative stress, lipid, nucleotide nucleoside and amino acid metabolisms, defense and signaling pathways. The combination of chemical modelling and metabolomic approach, used here for the first time, enlightened the influence of Zn present in the Al-Zn-In anodes.